1987
DOI: 10.1016/s0735-1097(87)80006-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency percutaneous transluminal coronary angioplasty in acute myocardial infarction: A 3 year experience

Abstract: In 151 patients experiencing acute myocardial infarction, emergency coronary angioplasty was performed as primary therapy. Overall, angioplasty was successful in 132 patients (87%); it was successful in 91 (85%) of 107 patients with a totally occluded infarct-related artery and in 41 (93%) of 44 patients with a subtotally occluded infarct-related artery. After successful angioplasty, mean residual stenosis was 29% (range 0 to 70). Eighteen patients were in cardiogenic shock (12%) including four patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…The success rate of angioplasty in this study (95%) was similar to that in other series [10,11] ; however, in our study, no patient underwent emergency bypass surgery following unsuccessful PCI.…”
Section: Discussionsupporting
confidence: 90%
“…The success rate of angioplasty in this study (95%) was similar to that in other series [10,11] ; however, in our study, no patient underwent emergency bypass surgery following unsuccessful PCI.…”
Section: Discussionsupporting
confidence: 90%
“…Other large series and recent randomized trials confirm this observation [7,[16][17][18],411. The absence of major intracranial bleeding after direct angioplasty with- out antecedent thrombolytic therapy is in contrast to the data from the thrombolytic trials [3-61.…”
Section: Discussionmentioning
confidence: 77%
“…Rothbaum et al [7] and Schroder et al [41] observed no cardiac rupture in patients after successful direct angioplasty for acute myocardial infarction without antecedent thrombolysis. Delayed healing and hemorrhage in the myocardium have been observed in patients who died after thrombolytic therapy but not after primary angioplasty for acute myocardial infarction [42-441, Successful direct angioplasty may limit the occurrence of hemorrhagic infarction and cardiac rupture.…”
Section: Discussionmentioning
confidence: 98%
“…Early and sustained patency of the infarct-related artery has been related to improved in-hospital and late survival (24,25), recovery of left ventricular function (24,(26)(27)(28), prevention of ventricular aneurysm formation (29), and cardiac rupture (30), and enhanced electrical stability (31). In addition, previous studies have demonstrated that only the acute restoration of TIMI grade 3 flow, present in ≈50% to 60% of vessels after fibrinolysis, is independently predictive of in-hospital survival and reduction in infarct size (26,32,33).…”
Section: Discussionmentioning
confidence: 99%